Test of the tonic effects of dragon fruit extract (cortice hylocereus polyrhizus) on white miice - Nurul Wahdah; Muhammad Riki Shindi Praristiya; Nur Mahdi (DSM Publisher, 2025)
Stamina is the body's resistance to fight fatigue within a certain time limit of a person's physical ability to survive at work. Dragon fruit skin contains flavonoid compounds, which have a tonic effect on male mice. This study aims to examine the tonic effect and the dosage used in male mice. We use the Natatory Exhaustion method to determine how drugs affect the coordinates of motion, especially when they reduce central nervous control. This research is an experimental research study. This study falls under the experimental research category. They were divided into 5 treatment groups: group I received Caffeine 100 mg/KgBB as a positive control, group II received Na-CMC as a negative control, and groups III, IV, and V received extract from dragon fruit peel (Cortice Hylocereus Polyhirzus) at doses of 750 mg/KgBB, 1000 mg/KgBB, and 1250 mg/KgBB. We administered oral treatments to each group. Next, observe the length of the mice's swimming duration. The test results data were analysed by the ANOVA analysis method. The results indicated that the extract from dragon fruit peel had a tonic effect on male mice, compared to positive and negative control doses. The three groups of dragon fruit peel extract had different swimming durations of 5.32 minutes, 5.45 minutes, and 5.92 minutes, respectively.